Frugal living in The "Tafseer al-Misbah" Perspective : Study of The Interpretation of QS. Al-Isra’ Verses 26-27 - Harahap, Anita Luthfiana; Rambe, Uqbatul Khoir (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2024)
The large amount of expenditure and lack of income during Covid 19 gave rise to the term or trend Frugal Living which is believed to have emerged to answer questions from several individuals or groups in allocating their finances so that there is no waste in everyday life. The reason is that the Frugal Living trend originates from the western region, which makes it difficult for many Indonesians, most of whom are Muslims, to follow this trend because they feel like it is western culture. Even though this trend is very good if carried out, this trend has also been explained in the Al-Qur'an surah Al-Isra' Verses 26-27 and this verse has been confirmed by modern interpretations, one of which is the Al-Misbah interpretation. This research also compares Quraish Shihab's thoughts in his interpretation of Al-Misbah with Buya Hamka in his interpretation of Al-Azhar through a comparison table. This research uses a qualitative descriptive approach with more emphasis on observing existing phenomena. The data sources used consist of the Koran, hadith, tafsir books, as well as several literature from books, journals and articles related to frugal living. The results of this research show that the frugal living trend has a very good impact if it is followed by individuals or groups because this is also stated in the Al-Qur'an surah Al-Isra' verses 26-27.